Perspectives on Science and Culture - Rutten, Kris; Blancke, Stefaan; Soetaert, Ronald (Comparative Cultural Studies, 2018)
"Edited by Kris Rutten, Stefaan Blancke, and Ronald Soetaert, Perspectives on Science and Culture explores the intersection between scientific understanding and cultural representation from an interdisciplinary perspective. Contributors to the volume analyze representations of science and scientific discourse from the perspectives of rhetorical criticism, comparative cultural studies, narratology, educational studies, discourse analysis, naturalized epistemology, and the cognitive sciences. The main objective of the volume is to explore how particular cognitive predispositions and cultural representations both shape and distort the public debate about scientific controversies, the teaching and learning of science, and the development of science itself.